Multi-country real-life experience of anti-vascular endothelial growth factor therapy for wet age-related macular degeneration. Issue 2 (5th September 2014) - Holz, Frank G; Tadayoni, Ramin; Beatty, Stephen; Berger, Alan; Cereda, Matteo G; Cortez, Rafael; Hoyng, Carel B; Hykin, Philip; Staurenghi, Giovanni; Heldner, Stephanie; Bogumil, Timon; Heah, Theresa; et al.
Abstract : Background/aims: Real-life anti-vascular endothelial growth factor (VEGF) therapy use in patients with wet age-related macular degeneration (wAMD) was assessed in a retrospective, observational study in Canada, France, Germany, Ireland, Italy, the Netherlands, UK and Venezuela. Methods: Medical records of patients with wAMD, who started ranibizumab treatment between 1 January 2009 and 31 August 2009, were evaluated. Data were collected until the end of treatment and/or monitoring or until 31 August 2011. Results: 2227 patients who received ≥1 anti-VEGF injection with a baseline visual acuity assessment and ≥1 postbaseline visual acuity assessment for the treated eye were evaluated. Visual acuity improved until about day 120; thereafter, visual acuity gains were not maintained. Mean change in visual acuity score from baseline to years 1 and 2 was +2.4 and +0.6 letters, respectively. Patients received a mean of 5.0 and 2.2 injections in the first and second year, respectively. There were substantial differences in visual outcomes and injection frequency between countries. More frequent visits and injections were associated with greater improvements in visual acuity. Conclusions: In clinical practice, fewer injections are administered than in clinical trials. Anti-VEGF treatment resulted in an initial improvement in visual acuity; however, this was not maintained over time. Trial registration number: NCT01447043.